PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THE OF POWER TWO TERHADAP PEMAHAMAN KONSEP MATEMATIKA DAN KECEMASAN MATEMATIKA DITINJAU DARI KEMAMPUAN AWAL MATEMATIKA SISWA DI SMP ISLAM PARISKIAN KOTA SERANG - Anggi Rahmani; Pinta Deniyanti Sampoerno; Lukman El Hakim (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2020)
ABSTRACTThe objective of this research was to find out the influence of cooperative learning method type of the power of two toward the ability of understanding mathematical concept and students’ mathematics anxiety. This research was conducted in SMP Islam Pariskian Kota Serang. This research used quasy experimental design. The data collecting technique are test and scale. The result of this research showed that (1) The ability of understanding mathematical concept between students that used cooperative learning model type of the power of two is higher than students that used conventional learning method; (2) there are interaction between learning method and the initial ability of mathematics toward the ability of understanding mathematical concept;  (3) the students’ ability of understanding mathematical concept with the high initial ability of mathematics that used cooperative learning model type of the power of two is higher than conventional learning method; (4) there is no difference of students’ understanding ability of mathematical concept with the low initial ability of mathematics, between students that used cooperative learning model type of the power of two is lower than students that used conventional learning method; (5) mathematics anxiety between students that used cooperative learning model type of the power of two is lower than students that used conventional learning method; (6) there are interaction between learning method and the initial ability of mathematics toward the anxiety of understanding mathematical concept; (7) the students’ anxiety of understanding mathematical concept with the high initial ability of mathematics that used cooperative learning model type of the power of two is lower than conventional learning method; (8) ) there is no difference of mathematics anxiety concept with the low initial ability of mathematics, between students that used cooperative learning model type of the power of two and conventional learning method.Keywords: The Power of Two, The Ability of Understanding Mathematical Concept, Mathematics AnxietyABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran kooperatif tipe the power of two terhadap kemampuan pemahaman konsep matematika dan kecemasan matematika siswa. Penelitian ini dilakukan di SMP Islam Pariskian Kota Serang. Metode yang digunakan dalam penelitian ini adalah quasi eksperimen. Teknik pengumpulan data yaitu tes dan skala. Hasil penelitian menunjukkan bahwa (1) Kemampuan pemahaman konsep matematika antara siswa yang mendapatkan model pembelajaran kooperatif tipe the power of two lebih tinggi daripada siswa yang mendapatkan model pembelajaran konvensional; (2) Terdapat interaksi antara model pembelajaran dan kemampuan awal matematika terhadap kemampuan pemahaman konsep matematika; (3) Kemampuan pemahaman konsep matematika siswa dengan kemampuan awal matematika tinggi yang belajar menggunakan model pembelajaran kooperatif tipe the power of two lebih tinggi dari siswa model pembelajaran konvensional; (4) Tidak terdapat perbedaan kemampuan pemahaman konsep matematika siswa dengan kemampuan awal matematika rendah, antara yang mendapatkan model pembelajaran kooperatif the power of two dengan model pembelajaran konvensional; (5) Kecemasan matematika antara siswa yang belajar menggunakan  model pembelajaran kooperatif tipe the power of two lebih rendah daripada siswa yang mendapatkan model pembelajaran konvensional; (6) Terdapat interaksi antara model pembelajaran dan kemampuan awal matematika terhadap kecemasan matematika; (7) Kecemasan matematika siswa dengan kemampuan awal matematika tinggi, siswa yang mendapatkan model pembelajaran kooperatif tipe the power of two lebih rendah daripada model pembelajaran konvensional; (8) Tidak terdapat perbedaan Kecemasan matematika siswa dengan kemampuan awal matematika rendah, antara yang mendapatkan model pembelajaran kooperatif tipe the power of two dengan model pembelajaran konvensional.Kata Kunci: The Power of Two, Kemampuan Pemahaman Konsep Matematika, Kecemasan Matematika